A Rural-Urban Metamorphosis in China: The Real Great Leap Forward? (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
After the first three decades of rapid urbanization, the Chinese government seems determined to amend the fifty-year old hukou system in order to achieve the ultimate goal of the National plan of urbanization, i.e. 900 million people living in urban areas by 2025. The hukou system would be abolished completely in â€œsmallâ€ cities and more gradually in cities referred to as â€œmediumâ€. A comparison between the physiographic situation of the Chinese territory of the late Nineteenth century and the situation of the current urban and rural areas strengthens the hypothesis of a complete restoration of macro historical regions to recover the structural constants capable of providing a solution to the massive problems of contemporary China and giving a meaning to its modernity.